The United Kingdom against Russia’s attempts to maintain the zones of influence on the example of the Ukrainian crisis - Jureńczyk, Łukasz (Przegląd Wschodnioeuropejski, 2021)
The subject of the paper are the United Kingdom’s actions against Russia’s attempts to maintain its zones of influence, based on the example of the Ukrainian crisis. The introduction consists of a synthetic outline of the geopolitical rivalry between Russia and Great Britain. The next section discusses the attitude of the United Kingdom towards Russia’s attempts to maintain its zones of influence in the 21st century. The main section of the paper focuses on the United Kingdom’s actions against Russia’s military policy in Ukraine. The main thesis of the paper assumes that during the Ukrainian crisis, the UK has taken the most far-reaching measures so far to oppose Russia’s attempts to maintain zones of influence. The consequence of this is a significant deterioration in Russian-British relations due to the Ukrainian crisis. The leading paradigm is structural realism. The method of text source analysis was used in the paper.